Effects of Stress in Adaptation to Undergraduate Life on Psychiatric Morbidity: Mediating Effects of Early Trauma and Adverse Family Factors - Zhang, Yingzhe; Coid, Jeremy; Liu, Xiang; Zhang, Yamin; Sun, Huan; Li, Xiaojing; Tang, Wanjie; Wang, Qiang; Deng, Wei; Zhao, Liansheng; Ma, Xiaohong; Meng, Yajing; et al. (Frontiers in Psychiatry, 2022)
Purpose: University students experience high levels of stress and the prevalence of depression is higher than in the general population. The reason is not clear. More effective interventions and better prevention are needed. Methods: We did annual cross-sectional surveys of Chinese undergraduates 2014-2018 (mean age 18.7 (SD 2.1), N=39,573). We measured adaptation to university life using the Adolescent Self-rating Life Events Checklist (ASLEC) and common mental disorders using standardised self-report instruments. Regression analyses identified associations between childhood maltreatment, current family problems, stress in adaptation to undergraduate life and psychiatric morbidity. Mediation analyses further tested relationships between these factors. Results: Childhood maltreatment, current family problems, stress in adaptation and psychiatric morbidity were all significantly associated with each other. The strongest association between childhood experiences and psychiatric morbidity was for sexual abuse and depression (OR=3.39, 95%CI: 2.38-4.83, p<0.001) and between stress from adaptation and somatic disorder (OR=4.54,95%CI: 3.62-5.68, p<0.001). Associations between childhood maltreatment and stress from university life were partly mediated by psychiatric morbidity. Associations between family problems and psychiatric morbidity were mediated by stress from university life. Conclusions: Stress from adaptation to university life and pressures from academic study exert stronger effects on psychiatric morbidity among students than childhood traumatic experiences and current family problems, although these factors are closely inter-related. Mental health services for students should focus on adaptation to university life and pressures from academic study as well as external factors of childhood trauma and family problems.